The effect of smoking on COVID‐19 severity: A systematic review and meta‐analysis. Issue 2 (13th August 2020) - Reddy, Rohin K.; Charles, Walton N.; Sklavounos, Alexandros; Dutt, Atul; Seed, Paul T.; Khajuria, Ankur
Abstract: Various comorbidities represent risk factors for severe coronavirus disease 2019 (COVID‐19). The impact of smoking on COVID‐19 severity has been previously reported in several meta‐analyses limited by small sample sizes and poor methodology. We aimed to rigorously and definitively quantify the effects of smoking on COVID‐19 severity. MEDLINE, Embase, CENTRAL, and Web of Science were searched between 1 December 2019 and 2 June 2020. Studies reporting smoking status of hospitalized patients with different severities of disease and/or at least one clinical endpoint of interest (disease progression, intensive care unit admission, need for mechanical ventilation, and mortality) were included. Data were pooled using a random‐effects model. This study was registered on PROSPERO: CRD42020180920. We analyzed 47 eligible studies reporting on 32 849 hospitalized COVID‐19 patients, with 8417 (25.6%) reporting a smoking history, comprising 1501 current smokers, 5676 former smokers, and 1240 unspecified smokers. Current smokers had an increased risk of severe COVID‐19 (risk ratios [RR]: 1.80; 95% confidence interval [CI]: 1.14‐2.85; P = .012), and severe or critical COVID‐19 (RR: 1.98; CI: 1.16‐3.38; P = .012). Patients with a smoking history had a significantly increased risk of severe COVID‐19 (RR: 1.31; CI: 1.12‐1.54; P = .001), severe or critical COVID‐19 (RR: 1.35; CI: 1.19‐1.53; P < .0001), in‐hospital mortality (RR: 1.26; CI: 1.20‐1.32; P < .0001), disease progression (RR: 2.18; CI: 1.06‐4.49; P = .035), and need for mechanical ventilation (RR: 1.20; CI: 1.01‐1.42; P = .043). Patients with any smoking history are vulnerable to severe COVID‐19 and worse in‐hospital outcomes. In the absence of current targeted therapies, preventative, and supportive strategies to reduce morbidity and mortality in current and former smokers are crucial. Highlights: The first high‐quality systematic review and meta‐analysis assessing the impact of smoking on COVID‐19 severity. To date, the largest meta‐analysis among peer‐reviewed literature assessing the impact of smoking on COVID‐19 severity, including 32, 849 hospitalised patients with COVID‐19. Patients who were current smokers had an increased risk of severe COVID‐19 and severe or critical COVID‐19. Patients with a smoking history had an increased risk of severe COVID‐19, severe or critical COVID‐19, in‐hospital mortality, disease progression and need for mechanical ventilation.